ELECTRONIC SYSTEM OF DIFFERENTIAL DIAGNOSIS OF CHRONIC DISEASES OF SMALL BRONCHI IN CHILDREN - Mustafayev, I.A. (World of Medicine and Biology, 2023)
The purpose of the study was to create an automated decision support system for the differential diagnosis of chronic nonspecific diseases of the small bronchi in children. It was based on a questionnaire used to study the prevalence of various forms of chronic nonspecific lung diseases and the features of the immunological status in children with chronic diseases of the small bronchi in children at the Research Institute of Pulmonary Diseases (Azerbaijan). The test cards were filled out and the correctness of the probability of pathology scores was assessed in 113 children with bronchial asthma, 139 children with chronic bronchiolitis and 103 children with bronchopulmonary dysplasia and with a history of bronchopulmonary dysplasia. A decision support system has been developed for the differential diagnosis of chronic nonspecific diseases of the small bronchi in children. The main feature of this technique is the ease of obtaining results after 3–5 minutes from the start of filling out the test card. The approbation of the developed automated system of early detection in children at the outpatient stage made it possible to clarify the form of diseases of the small bronchi, and to conduct informative research methods to confirm the diagnosis without using additional financial costs. For the first time, an automated decision support system has been developed for the differential diagnosis of chronic nonspecific diseases of the small bronchi in children. The application of the developed system has confirmed its practical significance in clarifying the form of chronic nonspecific diseases of the small bronchi in children.